ON THE ROLE OF TAXATION AND TAX CONTROL INSTITUTIONS IN IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT STRATEGY IN MODERN RUSSIA - Z. S. Yakupov (Russian Journal of Economics and Law, 2015)
Objective: to research scientific approaches to the institution of tax control, taking into account the basic theories and scientific concepts that affect the functioning of this institution. Methods: logical and statistical methods were applied, as well as methods of deduction and induction, scientific abstraction. Results: it is proved that sustainable economic development can be achieved by enhancing the financial and taxation mechanism. The institute of tax control is viewed as a softener of economic crises. Mechanisms are proposed to influence the crises and to minimize the losses of both taxpayers and the state. Scientific novelty: the model is proposed of the taxation tools and mechanisms for sustainable development of Russia. Practical value: the possibility to increase the value and efficiency of the taxation mechanisms for sustainable development.